2022
DOI: 10.3389/fcvm.2022.915903
|View full text |Cite
|
Sign up to set email alerts
|

Sinapic Acid Attenuated Cardiac Remodeling After Myocardial Infarction by Promoting Macrophage M2 Polarization Through the PPARγ Pathway

Abstract: BackgroundMacrophage polarization is an important regulatory mechanism of ventricular remodeling. Studies have shown that sinapic acid (SA) exerts an anti-inflammatory effect. However, the effect of SA on macrophages is still unclear.ObjectivesThe purpose of the study was to investigate the role of SA in macrophage polarization and ventricular remodeling after myocardial infarction (MI).MethodsAn MI model was established by ligating the left coronary artery. The rats with MI were treated with SA for 1 or 4 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Similarly, studies have reported the TAA efficacy in changing the weightage of the body and bulky liver formation in various rat trials [4,42,43]. These body/liver weightage modulations were almost normalized in SA-treated rats, which could be correlated with the dyslipidemia [44], anti-inflammatory [45], and antioxidant [46] bioactivities of SA as reported by previous researchers. Similarly, researchers have reported the SA efficacy in restoring the body and liver weightage to normal in dimethylnitrosamine (DMN)-induced chronic liver damage in rats [47].…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, studies have reported the TAA efficacy in changing the weightage of the body and bulky liver formation in various rat trials [4,42,43]. These body/liver weightage modulations were almost normalized in SA-treated rats, which could be correlated with the dyslipidemia [44], anti-inflammatory [45], and antioxidant [46] bioactivities of SA as reported by previous researchers. Similarly, researchers have reported the SA efficacy in restoring the body and liver weightage to normal in dimethylnitrosamine (DMN)-induced chronic liver damage in rats [47].…”
Section: Discussionsupporting
confidence: 74%
“…Heart tissue below the ligature line was removed and immersion-fixed in 4% paraformaldehyde for histological study. The heart is innervated by sympathetic, parasympathetic, and sensory fibers, of which sympathetic nerves are usually stained by TH [ 18 , 39 ]. Paraffin blocks of heart tissue were processed and cut into 4- μ m sections for immunohistochemistry for TH (1 : 2,000, CST, USA), and together with GAP43 [ 19 , 32 ] (1 : 200, Immunoway, USA), these two antibodies were used to assess cardiac sympathetic innervation.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that depleting macrophages using clodronate can reduce NGF levels in myocardial tissue, preventing excessive sympathetic innervation and improving myocardial electrical remodeling in the peri-infarct region [ 11 , 16 ]. Furthermore, promoting macrophage M2 polarization has been found to significantly decrease NGF levels [ 17 , 18 , 19 , 20 ]. Currently, macrophages are generally categorized as pro-inflammatory M1 or anti-inflammatory M2 macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…The oligonucleotides were synthesized using Gene Design (Suita, Japan). The primer sequences used were obtained from previous studies [10,[31][32][33] and are listed in Table 1.…”
Section: Gene Expression Of Macrophage Markers and Fibrosis-related F...mentioning
confidence: 99%
“…GGGTTCCATGGTGAAGTCAAC CACCTCTCAAGCAGAGCACAG [31] iNOS AGCATCCACGCCAAGAACG GTCTGGTTGCCTGGGAAAAT [32] IL-10 ACTGCTATGTTGCCTGCTCTTAC CAGTAAGGAATCTGTCAGCAGTATG [32] Arg1 ATTGGCAAAGTGATGGAAGAGAC CAAGACAAGGTCAACGCCAC [32] TGF-β AGAAGTCACCCGCGTGCTAAT CACTGCTTCCCGAATGTCTGA [33] Col 1a2 GCTTTGTGGATACGCGAACTC CCAGCATTGGCATGTTGCT [33] HRPT TGTTTGTGTCATCAGCGAAAGTG ATTCAACTTGCCGCTGTCTTTTA [10] TABLE 1: Primers designed for real-time PCR.…”
Section: Il-1βmentioning
confidence: 99%